THE DEVELOPMENT OF JAKARTA SEISMIC HAZARD MAP BY CONSIDERING THE EFFECTS OF DYNAMIC PARAMETERS AND TOPOGRAPHY OF BEDROCK ON SEISMIC-SITE RESPONSE AT SOIL SURFACE - Misliniyati, Rena
The study of microtremor array test conducted by Ridwan et al. (2016) has shown that the bedrock depth of Jakarta varies from 350 m in the south to a depth of 725 m in the northern part. This condition also shows that Jakarta is above the thickness sediment layer with shear wave velocities (Vs) ranging from 250 m/sec to 500 m/sec. This sedimentary layer is part of a large basin structure of Java Island, known as Sub-Basin Ciputat. Understanding that the bedrock depth (related to the bedrock topography and dynamic behavior of the overlying sediment layer) can affect the amplification of acceleration on the ground surface becomes very important in performing the seismic-site response analysis, especially for acceleration at long periods. Therefore, the seismic-site response analysis that involves the validated dynamic soil parameters and the effect of bedrock topography is needed to develop the earthquake hazard maps of Jakarta. The seismic hazard evaluation of Jakarta was carried out by using the verified parameters from previous studies. The parametric study of seismic response analysis based on Jakarta's site conditions and the validation study of soil models became a series of studies that initiated the seismic hazard evaluation in the Jakarta area. The implementation of the results of the preliminary studies had expected to provide the predictions of potential seismic hazards with more accuracy. Several parameters had reviewed in previous studies are height of soil element, the depth and shear wave velocity of bedrock, the plasticity of soil, the specification of input motion, the method of analysis, the target curves of shear modulus and damping ratio, and soil model. The model of soil geometry for the 2D numerical simulation was designed based on the bedrock depth profile developed from the results of the microtremor array measurement at 55 points by Ridwan et al. (2016). The profile of soil layers has been modeled based on 462 borehole data spread across the Jakarta area. This study simulated three input motion models designed by Asrurifak (2016) based on the disaggregation work of PSHA (Probabilistic Seismic Hazard Analysis) of Jakarta for a return period of 2500 years scaled to the target response spectra of PGA (Peak Ground Acceleration) according to SNI -1726-2012. The influence factor of Jakarta's bedrock topography had determined using the amplification ratio between 2D and 1D simulations. For this purpose, the seismic-site response analysis of Jakarta had performed in two numerical simulation models, namely 1D and 2D models. Then, the value of this factor had taken into account in developing seismic hazard maps of Jakarta for three models of input motion from different sources, namely megathrust, benioff, and shallow crustal. The results of a parametric study based on the local soil conditions of Jakarta show that all analytical parameters reviewed have a significant effect on the characteristics of spectral acceleration at the soil surface. The results of this study also recommend several criteria in seismic-site response analysis that had to apply for getting the predictions of results more accurately. The validation studies of several soil models had yielded the extended-hyperbolic MKZ model and the Sigmoidal-4 model as the selected models to be applied in the seismic-site response analysis of Jakarta in 1D and 2D numerical simulations, respectively. In this study, the 1D simulation had built using DEEP SOIL 7.1 code, while the 2D simulation used the FLAC 7.0 code. The results of seismic-site response analysis of Jakarta that simulated three models of input motion indicate the maximum factor of bedrock topography of 1.13 occurs at long period. This magnitude indicates that the bedrock topography model does not have a significant effect on the acceleration at the ground surface of Jakarta. The location of Jakarta is not at the edge of a large basin is predicted to cause the difference of spectral acceleration on the ground surface between the 1D and 2D simulations insignificantly. The amplification at long period is predicted to occur due to the condition of a thick sedimentary layer with low shear velocity, potentially propagating the strong earthquake. For the needs of evaluating the seismic hazard of Jakarta, the spectral accelerations at the ground surface also had presented in the contour maps of PGA values, SA 0.2 sec., SA 1.0 sec., and amplification factors for the three simulated models of input motion. In general, the potential assessment for seismic hazards in Jakarta based on seismic-site response analysis shows that the accelerations at the ground surface are smaller than the value required by SNI-1726-2012.